2017
DOI: 10.1002/vms3.56
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study of ectoparasites of horses in the western highlands of Cameroon

Abstract: To evaluate the prevalence of infestation of ectoparasites of horses, a total of 894 horses (367 males and 527 females), aged 1–7 years old were examined. Horses were groomed for collection of ectoparasites. Out of the horses examined, 164 came from Fundong, 80 from Acha, 30 from Fongo‐Tongo, 30 from Fokoue and 17 from Dschang, all of which were infested with ectoparasites. Five hundred and seventy‐three (573) horses came from Banso and 99.48% were infested by ectoparasites. From the results obtained, three sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 7 publications
0
7
2
Order By: Relevance
“…The significantly higher prevalence of tick infestation we recorded during the wet season may be due to high moisture content and lower temperature seen during the season, as rainfall has been reported to favour the development and abundance of ticks and as such have a positive effect on its prevalence (Greenfield, 2011). The statistically significant moderate and positive correlation between the co-diagnoses of babesiosis and tick infestation is attributed to the fact that ticks are the major vector for equine babesiosis (Kerber et al, 2009;Payne et al, 2017).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The significantly higher prevalence of tick infestation we recorded during the wet season may be due to high moisture content and lower temperature seen during the season, as rainfall has been reported to favour the development and abundance of ticks and as such have a positive effect on its prevalence (Greenfield, 2011). The statistically significant moderate and positive correlation between the co-diagnoses of babesiosis and tick infestation is attributed to the fact that ticks are the major vector for equine babesiosis (Kerber et al, 2009;Payne et al, 2017).…”
Section: Discussionmentioning
confidence: 66%
“…Mezgebu et al (2013) reported a similar finding to ours in terms of helminth infections and sex. The prevalence of tick infestation is influenced by the origin of the horse, age, body condition, breed, climate conditions and colour among other factors (Osman et al, 2006;Payne et al, 2017) and this may have resulted in the high prevalence we recorded in female horses as against male. The significantly higher prevalence of tick infestation we recorded during the wet season may be due to high moisture content and lower temperature seen during the season, as rainfall has been reported to favour the development and abundance of ticks and as such have a positive effect on its prevalence (Greenfield, 2011).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The tick species infesting horses found in this survey represent species that are prevalent on livestock throughout the Mediterranean area [ 21 – 25 ], and differ from tick species found on horses elsewhere [ 26 28 ]. Almost all ticks found were adults, which suggests that the immature stages infest other host species.…”
Section: Discussionmentioning
confidence: 99%
“…Equidae are used in many beneficial activities for human such as police services, agriculture and pharmaceutical purposes, in addition to competitive and non-competitive leisure pursuits [59]. Generally, Equidae, especially donkeys, play a significant role in the transmission of vector borne diseases by acting as a domestic reservoir and carrying vectors to a broad host range or even to human [1].…”
Section: Discussionmentioning
confidence: 99%